PERTANGGUNGJAWABAN HUKUM TERHADAP PENERBITAN SERTIFIKAT GANDA (STUDI DI BPN KOTA MATARAM) - NOVIE AFIF MAULUDIN; ANGGUN PUTRI SETYADI (GANEC SWARA, 2023)
The purpose of this is to find out how legal responsibility is for the issuance of multiple certificates (a study at BPN Kota Mataram). To answer the problem formulation the author uses normative legal research, with statutory approach methods (statute approach), and conceptual approach (conceptual approach) and case approach (case approach). As for the results of the study, it was concluded that legal responsibility for the issuance of multiple certificates (study at the Mataram City BPN) is to carry out non-litigation handling, namely at the Mataram City BPN Office and then can continue into the realm of litigation, namely in civil or state administrative courts, where BPN Mataram City as a party. This is done by referring to the applicable laws and regulations, namely the Regulation of the Minister of Agrarian Affairs/Head of the National Land Agency Number 9 of 1999 concerning Procedures for Granting and Canceling State Land Rights and Management Rights or Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the Land Agency National Republic of Indonesia Number 11 of 2016 concerning Settlement of Land Cases or Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 21 of 2020 Handling and Settlement of Land Cases. Which of the three regulations is used depends on when the land case is submitted to the land office. In cases with the decision of the Supreme Court of the Republic of Indonesia Number 45/G/2016/PTUN.MTR, accountability for multiple certificates refers to the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 11 of 2016 concerning Settlement of Land Cases.